Two new combinations of the Philippine Orchidaceae - Naive, Mark Arcebal K.; Alejandro, Grecebio Jonathan D. (Phytotaxa, 2018)
Recent studies (Schuiteman 2011, Xiang et al. 2013, Pridgeon et al. 2014) have proposed that Euphlebium (Kräenzlin) Brieger (1981: 722) and Grastidium Blume (1825: 333) should be congeneric with Dendrobium Swartz (1799: 82). Most names in Euphlebium and Grastidium have combinations in Dendrobium already. However, Euphlebium papilionaceum Cootes & M.A. Clem. (Cootes & Clements 2017) and Grastidium ginalopeziae Cootes, M.D. De Leon & Naive (Cootes et al. 2017) has not yet been formally transferred. Here we propose the new combination of these two species to merge under the genus Dendrobium.